2018
DOI: 10.1021/acs.jpcc.7b11767
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Boron-Very-Rich Boron Carbides: B12 Icosahedra Linked through Bent CBB Chains

Abstract: The atomic structures of boron carbide in the regime below ~13.3 at.% C (known as boron-veryrich boron carbide, BvrBC) have not previously been reported due to the complexity of the structure and bonding. We report here the atomistic crystal structures for stoichiometry B 14 C, with only 6.7 at.% C, predicted using quantum mechanics (QM) at the PBE level. We find that B 14 C consists of one B 12 icosahedral cluster and one C-B-B chain per unit cell. The C-B-B chain can be linear or bent, leading to two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The boron carbides exist as a single-phase material from about 8 at.% carbon to about 20 at.% carbon [ 4 , 5 ]. Very few studies have reported on the atomic structures of boron carbide in the regime below ~13.3 at.% C (known as boron–very rich boron carbide, BvrBC) due to the complexity of the structure and bonding [ 9 , 54 ]. A model based on XRD data proposes that the 20 at.% carbon composition is made up of B 12 icosahedra and carbon–carbon–carbon (CCC) chains [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The boron carbides exist as a single-phase material from about 8 at.% carbon to about 20 at.% carbon [ 4 , 5 ]. Very few studies have reported on the atomic structures of boron carbide in the regime below ~13.3 at.% C (known as boron–very rich boron carbide, BvrBC) due to the complexity of the structure and bonding [ 9 , 54 ]. A model based on XRD data proposes that the 20 at.% carbon composition is made up of B 12 icosahedra and carbon–carbon–carbon (CCC) chains [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, no trace of boron oxide or residual carbon is found in any pattern. We tried to find the new theoretically predicted B 14 C but our fitting is not compatible with their structural parameters and symmetry 26 .
Figure 1XRD patterns of the boron carbide ceramics grown at ( A ) 150, ( B ) 300, ( C ) 500 and ( D ) 750 mm/h. An example of the overlapped peaks of boron carbide and metallic boron are shown at ~23° in inset.
…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the Pugh’s ductility indexes (B/G) is frequently used to indicate the ductility of compounds [ 24 , 37 ]. It is supposed that for brittle compounds, B/G is smaller than 1.75 (for diamond B/G = 0.8) and for metallic compounds, B/G is greater than 1.75 (for Al B/G = 2.74) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the deformation mechanisms of boron carbide with different carbon contents is not the same [ 16 , 17 , 18 , 19 ]. An et al [ 22 , 23 , 24 ] studied the deformation mechanism of boron carbides with different carbon contents under shear deformation, corresponding to B 12 C 3 (B 4 C) and B 13 C 2 and B 14 C stoichiometries. The deformation mechanism of B 4 C involves two steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation